DUKUNGAN SOSIAL DAN POST-TRAUMATIC STRESS DISORDER PADA REMAJA PENYINTAS GUNUNG MERAPI - Tentama, Fatwa (Faculty of Psychology, Diponegoro University, 2014)
AbstractThe greatest eruption of the Mount Merapi took place in the past four-years. Various psychological problems were reported since then, one of which was post-traumatic stress disorder (PTSD). The survivors of Mt. Merapi eruption needed social support from the significant others. This study aims to empirically test the correlation between social support and PTSD on adolecescents survivor of Mt. Merapi’s eruption. Thirty junior high school students of SMP Negeri I Turi, Sleman, Yogyakarta, aged 12-15 years participated the study. Two scales were used to collect data: the Post-traumatic Stress Disorder Scale (15 items; α = 0.89) and Social Support Scale (16 items; α = 0.88). The results of product moment correlation analysis of Pearson revealed a negative significant correlation between social support and PTSD (r = -0.42; p = 0.02). This finding indicated that the less social support adolescent has received, the more severe they reported post-traumatic stress disorders.